Characterization of Al/B4C-Y2O3 hybrid composites produced by vacuum hot pressing combined with Al2O3-Y2O3 interaction - Bayrak, Yahya; Kisasoz, Burcin Ozbay; Tarakci, Gurkan; Kisasoz, Alptekin (ELSEVIER SCI LTD, 2024)
In this study, the Al/B4C/Y2O3 hybrid composites were produced by Al2O3 and Y2O3 interaction via hot pressing. Moreover, the influence of Y2O3 on the properties of Al/B4C 10 wt% was investigated. The hot pressing was performed at 600.C with pre-oxidized aluminium powder to produce the composites. The microstructure analyses revealed that Al/B4C/Y2O3 hybrid composite production was achieved by Al2O3 and Y2O3 interaction, and the Y4Al2O9 (YAM) phase was obtained in the Al-B4C/Y2O3 5 % sample. The Y2O3 addition increased the porosity content of the Al/B4C structure. However, wear rate and corrosion resistance of the Al/B4C were enhanced owing to the presence of Y2O3. The wear rate of Al/B4C was reduced from 26.55 center dot 10 7 cm(3)/Nm to 5.68 center dot 10 7 cm(3)/Nm at 15 N test load. The increasing Y2O3 content and the formation of the Y4Al2O9 decreased the corrosion rate of the Al/B4C fom 0.0179 mm/year to 0.0051 mm/year. Also, corrosion damage was shifted from the matrix to the reinforcement zone in Al-B4C/Y2O (3)5 % sample, and the aluminium was protected owing to the presence of Y2O3 and Y4Al2O9.
Keywords: Hot pressing; Composites; Y2O3; Structural applications; YTTRIUM-ALUMINUM-GARNET; MECHANICAL-PROPERTIES; BEHAVIOR; MICROSTRUCTURE; WEAR; Materials Science